How Leading Economic Sectors Stimulate Economic Growth, Income and Labor Absorption? Input - Output Approach - Mardalena, Mardalena; Adji, Ardi; Suhel, Suhel; Andaiyani, Sri (International Journal of Economics and Financial Issues, 2019)
Indonesia as emerging market economics provide some policies that leads to pro-growth, pro-poor and pro-job. This study aims to analyze which sectors are able to stimulate economic growth, household income, and labor absorption in South Sumatera Province. We analyze Input-Output Analysis which was estimated using RAS method. The analysis of output multiplier number used in this study to determine which sectors trigger the economic growth. At other hand, the income multiplier number is used in determining which sectors generate the income level, while the employment multiplier number determines he highest labor-absorbing economic sector. In the result, there are five economic sectors which is the main driver of economic growth : (1) Industry of coal and fuel refinery; (2) Industry of metal, computers, electronics, optical and electricity equipment; (3) industry of foods and beverages; (4) Farms and livestocks; (5) Electricity and gas installment, ice production, water supply and recycle of garbage. The five leading economic sectors generating the labor income increasement are : (1) administration of government, national defense and mandatory social security; (2) service of education, health and social activities; (3) rail transportation; (4) service of financial brokerage, insurance, pension fund and financing supports; (5) mining and quarrying of miscellaneous materials. The five leading economic sectors generating the absorption of labor force are : (1) other services; (2) plantation; (3) farmings and livestocks; (4) foods agricultural; and (5) forestry and logging. The direction of economic transformation in South Sumatera Province should tribute attention to the importance of pro-growth, pro-poor, pro-job policy. Keywords: leading economic sectors; pro-growth, pro-poor and pro-job policy JEL Classifications: R10, R11, R15 DOI: https://doi.org/10.32479/ijefi.6406